PERSEPSI MASYARAKAT TERHADAP RENCANA PENDIRIAN PERTAMBANGAN TIMAH HITAM (Pb) DI HULU SUNGAI AEK LATONG KECAMATAN SIABU KABUPATEN MANDAILING NATAL SUMATERA UTARA - Mardana Hasian; surtani surtani (JURNAL BUANA, 2019)
The purpose of this research was to describe the perceptions of the people of Lumban Dolok, Sinonoan and Tangga Bosi I about planning the establishment of plumbum mining (Pb) in the upstream of the Aek Latong River, Siabu District, Mandailing Natal Regency, North Sumatra. This research used quantitative descriptive methods. The population in this study were all family heads (KK) in Siabu District. The proportional random sampling technique was used to determine the samples. Analysis and measurement techniques used percentage techniques and Likert scale. While the data used is the number of house hold (KK). This study found those: 1) Society tended to be classified as less agree or 18 KK (39.44%), 2) The second highest number of society perceptions is the category that is quite agree, which is 17 KK (23.94%), 3) There are 15 KK (21.13%) categorized as agree about planning the establishment of plumbum mining (Pb), 4) The people who choose as strongly agree are 10 KK (14.08%). (5) There is only 1 KK (1.41%) who do disagree with the planned establishment of mining in the upstream of Aek Latong River.